2014
DOI: 10.1038/nrneurol.2014.60
|View full text |Cite
|
Sign up to set email alerts
|

Genetic testing in the epilepsies—developments and dilemmas

Abstract: In the past two decades, the number of genes recognized to have a role in the epilepsies has dramatically increased. The availability of testing for epilepsy-related genes is potentially helpful for clarification of the diagnosis and prognosis, selection of optimal treatments, and provision of information for family planning. For some patients, identification of a specific genetic cause of their epilepsy has important personal value, even in the absence of clear clinical utility. The availability of genetic te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 63 publications
(60 reference statements)
3
60
0
6
Order By: Relevance
“…Their approach parallels the approach undertaken now in the clinic, which is far from perfect but offers the possibility of genetic diagnosis to an increasing number of children with severe early onset epilepsy (8). Their work nicely demonstrates the value of collaborative sequencing efforts and functional validation of suspected variants.…”
Section: Hcn1 Gain-of-function Mutations -A New Cause Of Epileptic Enmentioning
confidence: 86%
“…Their approach parallels the approach undertaken now in the clinic, which is far from perfect but offers the possibility of genetic diagnosis to an increasing number of children with severe early onset epilepsy (8). Their work nicely demonstrates the value of collaborative sequencing efforts and functional validation of suspected variants.…”
Section: Hcn1 Gain-of-function Mutations -A New Cause Of Epileptic Enmentioning
confidence: 86%
“…Many previous studies reported that up to 50% of patients with epilepsy were treated at least intermittently with more than one AED. In these cases, identification of a specific genetic cause could have a significant personal value, even in the absence of clear clinical utility (30)(31)(32). Assortment of AED to control epileptic attack should be based on several factors, including mechanism of action, side effect profile, and AED-AED interactions (7,33).…”
Section: Discussionmentioning
confidence: 99%
“…Not unlike other genetically determined disorders, the value of genetic testing depends on the following four factors: analytic validity, clinical validity, clinical utility, and personal utility [29].…”
Section: Circumstances Of Genetic Testingmentioning
confidence: 99%